The Portuguese, Slovenian and French Presidencies 2007- 2008 - A Sea Change in European Spatial Planning? - Andreas Faludi (European Journal of Spatial Development, 2009)
This paper gives an account of the successive presidencies of Portugal, Slovenia and France. It asks whether European spatial planning is undergoing a sea change: a transformation caused by the unintentional cumulative impact of pragmatic organisational changes. The paper also invokes the notion of a ‘two-level game’ to characterise the situations in which European planners constantly have to look over their shoulders to how their own national constituencies operate. Against this backdrop, the paper establishes that, albeit under the territorial cohesion flag, there has indeed been a sea change in the institutionalisation, not in a formal but rather in an informal sense. The new arrangements feature semi-permanent working groups with a lifespan extending beyond presidential terms. In addition there is now substantial member state input, with meetings of the National Territorial Cohesion-related Contact Points the functional equivalent of the Committee on Spatial Development from the ESDP era. The professionalism of the whole process, in which one can safely assume that close to one hundred experts from all over Europe have taken part, is clear and particularly so since the Portuguese Presidency where focus was placed on the plans and ideas of the Commission, in particular the Green Paper on Territorial Cohesion, and on territorial cohesion policy as giving strength to cohesion policy as such. This emphasis – other than under the German Presidency – on cohesion policy is not really surprising. Portugal is one of its beneficiaries. Slovenia is the paragon among new member states and one of the chief priorities of its presidency has been to launch the discussion on the Lisbon Strategy – now the umbrella under which EU cohesion policy comes – post-2010. France regards itself – rightly – as a leading light in regional policy and planning: Indeed it practically invented EU cohesion policy. This all makes the renewed focus on EU policy understandable and augurs well for a more cooperative relationship in future between the member states and the Commission in this area.